Learning Media Development of Analyzing Poetry-Building Element Using Sparkol Videoscribe - Septianti, Anggi Surya; Purnomo, Mulyadi Eko; Indrawati, Sri (Jurnal Pendidikan Indonesia, 2020)
This study aims to develop learning media to analyze the building blocks of poetry by using sparkol videoscribe in 10th grade students. This research is a development research (R&D). This research method is used to produce certain products, and test the effectiveness of these products. Data collection techniques used were interviews, questionnaires, and learning outcomes tests. The data analysis technique was carried out by analyzing the questionnaire which was seen from the results of the high and low percentage of the needs desired by students and the next teacher. Based on the results of product trials, it shows an increase in learning outcomes of 36.76, with a pretest mean of 41.96 while postest was 78.92. Based on these findings it can be concluded that the development of learning media to analyze the building blocks of poetry using sparkol videoscribe has an effect on the learning outcomes of 10th grade students.